2017
DOI: 10.1038/nclimate3277
|View full text |Cite
|
Sign up to set email alerts
|

Weakening temperature control on the interannual variations of spring carbon uptake across northern lands

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 211 publications
(170 citation statements)
references
References 37 publications
9
158
2
1
Order By: Relevance
“…Our work reveals a temperature‐dependent shift in the autumn carbon cycle similar to that which has occurred during the main growing season over the last three decades (Peñuelas et al, ; Piao et al, ). This finding suggests a changing paradigm for the impact of temperature on the northern high‐latitude carbon cycle.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Our work reveals a temperature‐dependent shift in the autumn carbon cycle similar to that which has occurred during the main growing season over the last three decades (Peñuelas et al, ; Piao et al, ). This finding suggests a changing paradigm for the impact of temperature on the northern high‐latitude carbon cycle.…”
Section: Resultssupporting
confidence: 70%
“…Evidence has recently emerged to indicate that the response of the carbon cycle to climate change since the late 1990s has been different from that in the previous few decades (Ballantyne et al, ; Peñuelas et al, ; Piao et al, , ). It has long been assumed that warming advances spring phenology and increases ecosystem carbon uptake (Keeling et al, ; Richardson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The failure to reproduce the positive sign of γ int in wet season and the seemingly oversensitivity of GPP to interannual temperature variations (roughly two times more in the carbon cycle models compared to MTE for GPP) in dry season highlights the need for further model benchmarking and improvements. As drought length and intensity are projected to change (Colins et al,; Park et al., ), the tropical carbon cycle may become more dominated by interannual temperature variations, which is in contrast to the higher northern lands (Piao et al., ). Furthermore, improving model skills in simulating the response to such climatic change is required in order to project the changing tropical carbon cycle accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the overall warming trend may lead to earlier seasonal plant growth; however, incomplete development of green tissues exposed to colder environments may negatively influence tree growth and carbon storage [6]. To the contrary, some researchers concluded that increased temperature and longer growing seasons will increase the NPP and enhance carbon uptake of boreal forests; this response, however, was weak in interannual variations [64]. Boreal forests store vast amounts of carbon in soil, but the temperature effects on soils are challenging to measure.…”
Section: The Effects Of the Climate Variables On Carbon Cycling In Momentioning
confidence: 95%